Involvement of Cell Proliferation Induced by Dual Intracellular Signaling of HB-EGF in the Development of Colitis-Associated Cancer during Ulcerative Colitis. (29th September 2010) - Tanida, Satoshi; Mizoshita, Tsutomu; Mizushima, Takashi; Shimura, Takaya; Kamiya, Takeshi; Kataoka, Hiromi; Joh, Takashi
Abstract : In ulcerative colitis (UC), the duration and severity of inflammation are responsible for the development of colorectal cancer. Reactive oxygen species (ROS), reactive nitric metabolites (RNMs) and interleukin (IL)-8, released by epithelial and immune cells, are involved in the pathogenesis of colitis-associated cancer. Nitric oxide and peroxynitrite activate epidermal growth factor receptor (EGFR), and therapeutic agents targeted towards EGFR are currently used to treat advanced colorectal cancer. IL-8 (a G-protein coupled receptor (GPCR) agonist), which is involved in neutrophil recruitment and activation in persistent active colitis, also promotes cleavage of the proheparin-binding epidermal growth factor-like growth factor (proHB-EGF) through a disintegrin and metalloproteinase (ADAM). The cleaved HB-EGF and C-terminal fragments (intracellular CTF) regulate proliferation via EGFR activation and nuclear export of promyelocytic leukemia zinc finger, transcription repressor, respectively. Here, we focus on the mechanisms by which RNM- and IL-8-induced EGF signaling regulate cell proliferation during the development of colitis-associated cancer.